pre cal

posted by .

Factor completely: 3x^2(4x2 + 1)^8 + 64x^4(4x2 + 1)^7.

  • pre cal -

    x^2(4x^2+1)^7(76x^2+3)

  • pre cal -

    how did you solve this??? I am so los.

  • pre cal -

    3x^2(4x2 + 1)^8 + 64x^4(4x2 + 1)^7

    Notice that x^2 is a factor of each term, and so is a power of (4x^2+1)
    So, factoring them out, we have

    x^2 (4x^2+1)^7 (3(4x^2+1)+64x^2)
    3(4x^2+1)+64x^2 = 12x^2+3+64x^2 = 76x^2+3

    and that's Tony's answer

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    -5(3x - 7) Sorry I meant this one:-4x2(3x2 - x + 1) *Your supposed to do the FOIL Method! -12x4 + 4x3 - 4x2
  2. algebra

    factor the expression 4xsquared+35x+24 my answer: (4x+3)(x-8) 4x2 +35x+24= 24 = 2x12 24 = 4x6 24 = 8x3***** (4x+3)(X+8) 4X2 + 3X + 32X +24 + 4XSQ. + 35X + 24
  3. Math

    How do I mutliply the following; (4x2+3x-3)(4x2+3x-3)
  4. need help

    factor completely 4x2^-8x
  5. maths

    Using the digits 1, 2, 3 & 4 each once only, and as many +, -, x, / and brackets as you need, try to make as many different numbers as you can, starting at 0, 1, 2 .... Which is the first number that you cannot make?
  6. Math

    Using the digits 1, 2, 3 & 4 each once only, and as many +, -, x, / and brackets as you need, try to make as many different numbers as you can, starting at 0, 1, 2 .... Which is the first number that you cannot make?
  7. calculus

    Consider the function below. f(x) = 4x2 - 5x (a) Find f '(2). (b) Use the answer in part (a) to find an equation of the tangent line to the parabola y = 4x2 - 5x at the point (2, 6). y =
  8. Algebra

    1. What polynomial has a graph that passes through the given points?
  9. Pre cal

    Fine a third degree polynomial function f(x) with real coefficients that has 4 and 2i are zeros and such that f(-1) =-50 4 21 -2i (x-4)(x-2i)(x+2i) (x-4)(x2+4) x3-16+4x-4x2 (x3-4x2+4x-16) -50=a(-1-4-4-16) -50=.25 a=2 Not understanding, …
  10. Math

    Prove 3(x+1)(x+7)-(2x+5)² is never positive So, 3(x+1)(x+7)-(2x+5)(2x+5) =3(x²+8x+7)-(4x²+20x+25) =3x²+24x+21-4x²-20x-25 =-x²+4x-4

More Similar Questions